Stabilizing role of structural elements within the 5´ Untranslated Region (UTR) and gag sequences in Mason-Pfizer monkey virus (MPMV) genomic RNA packaging - Kalloush, Rawan M. (RNA Biol, 2019)
The Mason-Pfizer monkey virus (MPMV) genomic RNA (gRNA) packaging signal is a highly-structured element with several stem-loops held together by two phylogenetically conserved long-range interactions (LRIs) between U5 and gag complementary sequences. These LRIs play a critical role in maintaining the structure of the 5´ end of the MPMV gRNA. Thus, one could hypothesize that the overall RNA secondary structure of this region is further architecturally held together by three other stem loops (SL3, Gag SL1, and Gag SL2) comprising of sequences from the distal parts of the 5´untranslated region (5ʹ UTR) to ~ 120 nucleotides into gag, excluding gag sequences involved in forming the U5-Gag LRIs. To provide functional evidence for the biological significance of these stem loops during gRNA encapsidation, these structural motifs were mutated and their effects on MPMV RNA packaging and propagation were tested in a single round trans-complementation assay. The mutant RNA structures were further studied by high throughput SHAPE (hSHAPE) assay. Our results reveal that sequences involved in forming these three stem loops do not play crucial roles at an individual level during MPMV gRNA packaging or propagation. Further structure–function analysis indicates that the U5-Gag LRIs have a more important architectural role in stabilizing the higher order structure of the 5´ UTR than the three stem loops which have a more secondary and perhaps indirect role in stabilizing the overall RNA secondary structure of the region. Our work provides a better understanding of the molecular interactions that take place during MPMV gRNA packaging.